Levonorgestrel Intrauterine System Mirena: An Update - Siddiqui, Maruf; Hossain, Fawzia; Banu, Lailaa (Bangladesh Journal of Obstetrics & Gynaecology, 2009)
Mirena is a levonorgestrel-releasing intrauterine system. Apart from being a reliable contraception, Mirena is now widely indicated for its non contraceptive benefits which include treatment of menorrhagia, dysmenorrhoea, premenstrual symptoms, fibroids, adenomyosis, endometriosis etc. It is now used even for hormone replacement therapy. This review article tries to explore different aspects of Mirena for treatment of menorrhagia compared to other available methods based on recent trials. doi: 10.3329/bjog.v23i1.3054 Bangladesh J Obstet Gynaecol, 2008; Vol. 23(1) : 25-31